2011
DOI: 10.1002/ejoc.201001620
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and Synthetic Applications of the Heck–Matsuda Reaction: The Return of Arenediazonium Salts to Prominence

Abstract: This review highlights the potential and the versatility of arenediazonium salts as viable alternatives to conventional aryl halides and oxygen-based electrophiles for Pd-catalyzed Heck reactions. It also presents an overview of the field over the last decade, including some historical perspective of the Heck-Matsuda (HM) reaction with general considerations regarding reaction conditions, type of catalysts used, and the application of arenediazonium salts as reagents for the HM arylation of several types of al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
112
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 290 publications
(133 citation statements)
references
References 123 publications
2
112
0
Order By: Relevance
“…This result was intriguing and different reaction conditions were evaluated to minimize its formation. Several palladium sources (Pd(TFA) 2 , Pd(OAc) 2 , Pd(dba) 2 , Pd 2 (dba) 3 ), temperature (r.t. to 60ºC), base (DTBMP, ZnCO 3 and NaOAc), and olefin/salt ratio were screened in order to find out the best reaction conditions. After some experimentation, a reasonable result was achieved employing Pd(dba) 2 as the catalyst, ZnCO 3 or NaOAc as base at 60 o C leading to the product mixture (4/5/7) in a ratio of 2/6/1 in an total yield slightly greater than 50%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This result was intriguing and different reaction conditions were evaluated to minimize its formation. Several palladium sources (Pd(TFA) 2 , Pd(OAc) 2 , Pd(dba) 2 , Pd 2 (dba) 3 ), temperature (r.t. to 60ºC), base (DTBMP, ZnCO 3 and NaOAc), and olefin/salt ratio were screened in order to find out the best reaction conditions. After some experimentation, a reasonable result was achieved employing Pd(dba) 2 as the catalyst, ZnCO 3 or NaOAc as base at 60 o C leading to the product mixture (4/5/7) in a ratio of 2/6/1 in an total yield slightly greater than 50%.…”
Section: Resultsmentioning
confidence: 99%
“…1 The conventional Heck reaction despite its efficiency and robustness, carries some limitations which can be overcome with the use of aryl diazonium salts. 2 Inspired by the growing interest of the pharmaceutical industry in optically pure compounds, the Correia´s group has developed of enantioselective Heck-Matsuda reaction. 4 In the present study the asymmetric arylation of indenes via the Heck-Matsuda reaction will be explored aiming at its application to the synthesis of pharmacologically active compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Since the early reports by Suzuki and Miyaura on the cross-coupling reaction a tremendous development has taken place in terms of substrate flexibility and reaction conditions. A range of different catalysts and conditions are now available for the successful cross-coupling of halides, triflates, O-tosylates, and diazonium salts upon reaction with boronic acid, boronates, and trifluoroborates [3,7,[11][12][13][14][15]]. …”
Section: Introductionmentioning
confidence: 99%
“…It has emerged as a greener, faster and more practical alternative to the conventional Heck protocols. 1 In 2007, we presented the application of an efficient regio-and stereoselective Heck-Matsuda (HM) arylation of N-carbomethoxy-L-3-dehydroproline methyl ester (1) with arenediazonium tetrafluoroborates in the syntheses of aryl kainoids with potent neurotoxic activities. 2 Recently, new studies using arenediazonium salts containing EWG showed an unexpected inversion of the enantioselectivity in these substrate directable HM reactions.…”
Section: Introductionmentioning
confidence: 99%